Vaccine for Biomedics: A Second Revised Edition of Vaccinology at a Glance - Shnawa, Ibrahim Mohammed Saeed (Vaccine for Biomedics: A Second Revised Edition of Vaccinology at a Glance, 2022)
The book vaccine for biomedics is a second revised and updated version of the first edition of Vaccinology at a Glance, Lap Lambert academic Publisher Germany. The updated version was ensemble three parts, the introductory, the vaccine and the vaccine update. The text organized in 25 chapters covering essential vaccinology, vaccine technology and vaccine update. The reverse vaccine, mucosal vaccine and the corona vaccines were the add in the updated version. It is intended to be of use for biomedics professionals, and vaccine researchers.